Endogenous cytokinin in developing kiwifruit is implicated in maintaining fruit flesh chlorophyll levels - Pilkington, Sarah M. (Oxford University Press, 2013)
BACKGROUND AND AIMS: Green kiwifruit (Actinidia deliciosa) retain high concentrations of chlorophyll in the fruit flesh, whereas in gold-fleshed kiwifruit (A. chinensis) chlorophyll is degraded to colourless catabolites during fruit development, leaving yellow carotenoids visible. The plant hormone group the cytokinins has been implicated in the delay of senescence, and so the aim of this work was to investigate the link between cytokinin levels in ripening fruit and chlorophyll de-greening. METHODS: The expression of genes related to cytokinin metabolism and signal transduction and the concentration of cytokinin metabolites were measured. The regulation of gene expression was assayed using transient activation of the promoter of STAY-GREEN2 (SGR2) by cytokinin response regulators. KEY RESULTS: While the total amount of cytokinin increased in fruit of both species during maturation and ripening, a high level of expression of two cytokinin biosynthetic gene family members, adenylate isopentenyltransferases, was only detected in green kiwifruit fruit during ripening. Additionally, high levels of O-glucosylated cytokinins were detected only in green kiwifruit, as was the expression of the gene for zeatin O-glucosyltransferase, the enzyme responsible for glucosylating cytokinin into a storage form. Season to season variation in gene expression was seen, and some de-greening of the green kiwifruit fruit occurred in the second season, suggesting environmental effects on the chlorophyll degradation pathway. Two cytokinin-related response regulators, RRA17 and RRB120, showed activity against the promoter of kiwifruit SGR2. CONCLUSIONS: The results show that in kiwifruit, levels of cytokinin increase markedly during fruit ripening, and that cytokinin metabolism is differentially regulated in the fruit of the green and gold species. However, the causal factor(s) associated with the maintenance or loss of chlorophyll in kiwifruit during ripening remains obscure.